Investigation of pre-service TESOL teachers’ perceptions towards multimedia– based textbook development and usage - Smagulova, Gulnur; Sarzhanova, Galiya; Romanenko, Svetlana; Bobesh, Roza; Jangeldinova, Saltanat (Journal of Education and e-Learning Research, 2024)
The purpose of the study is to present the results of investigating pre-service teachers’ perceptions of their readiness to develop and use multimedia-based English language training textbooks. The dimensional structure of the designed readiness is regarded as a complex personal integrative quality. A corresponding survey questionnaire is compiled to determine its content. The study included 81 senior students from the foreign language faculty at Karaganda Buketov University. The research's methodology included statistical analysis of quantitative data, experimental training and participant self-assessment questionnaires. Preliminary tests were conducted in both the experimental and control groups aimed at identifying participants’ perceptions of their initial level of readiness for the development and use of multimedia-based textbooks. Participants in the experimental group participated in an experimental course on technology development and the use of multimedia-based textbooks with the presentation of their final project. When the teaching period was over, the post-test was taken. The results demonstrated the efficiency of the complex assessment of readiness in the mentioned area enabling the definition and correction of gaps in its structural content. The designed course proved its effectiveness in practice as asserted by the post-test scores.